2020
DOI: 10.1159/000510789
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Total Serum IgE in Adults: The Role of Obesity and Related Metabolic Disorders

Abstract: <b><i>Background and Aim:</i></b> Few reports have investigated the association between metabolic abnormalities (obesity and related metabolic syndrome) and total serum IgE concentrations. <b><i>Methods:</i></b> This cross-sectional study included a random sample of 1,516 adult individuals (44.7% men, aged 18–91 years, median 52 years) from a single municipality in Spain. Serum IgE was measured in the ADVIA Centaur system. Atopy was defined by the presence of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…Despite the IgE ≥ 75 IU/mL threshold was recently used in the clustering of severe asthma [ 29 ] and IgE ≥ 100 IU/mL has been covered in the definition of T2-high allergic inflammation [ 19 ], we deliberately ruled out the serum total IgE content from our patients’ stratification. Total IgE levels have been independently associated, in non-atopic individuals, with cigarette smoking and alcohol consumption, while variable concentrations have also been detected in aging, autoimmunity, immunodeficiency (e.g., Job’s Syndrome), cancer, obesity, parasitic infection, and metabolic syndrome [ 30 ]; otherwise, allergic patients may have low total IgE levels. The IgE clinical utility has been judged modest in clinical practice [ 31 ]; hence, total IgE cannot be considered a reliable biomarker for T2-high allergic phenotyping [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the IgE ≥ 75 IU/mL threshold was recently used in the clustering of severe asthma [ 29 ] and IgE ≥ 100 IU/mL has been covered in the definition of T2-high allergic inflammation [ 19 ], we deliberately ruled out the serum total IgE content from our patients’ stratification. Total IgE levels have been independently associated, in non-atopic individuals, with cigarette smoking and alcohol consumption, while variable concentrations have also been detected in aging, autoimmunity, immunodeficiency (e.g., Job’s Syndrome), cancer, obesity, parasitic infection, and metabolic syndrome [ 30 ]; otherwise, allergic patients may have low total IgE levels. The IgE clinical utility has been judged modest in clinical practice [ 31 ]; hence, total IgE cannot be considered a reliable biomarker for T2-high allergic phenotyping [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the National Health and Nutrition Examination Survey 2005-2006 suggested that vitamin D deficiency is associated with higher levels of IgE sensitization in children and adolescents (47). However, for a long time obesity has not been considered a modulator of IgE serum concentrations (48) 1).…”
Section: Discussionmentioning
confidence: 99%
“…(25) Um achado previamente descrito, embora pouco estudado, foram níveis mais elevados de IgE total em pacientes obesos. (26) A FeNO também é um biomarcador importante não apenas para identificar o fenótipo inflamatório, mas também como preditor da resposta ao tratamento com anti-IL-4/IL-13. (27) Uma das formas de determinar a FeNO é por meio de um dispositivo portátil de fácil manuseio (28) na prática clínica.…”
Section: Discussionunclassified
“… 25 A previously described albeit poorly studied finding was higher total IgE levels in obese patients. 26 …”
Section: Discussionmentioning
confidence: 99%